A NOVEL CONTROL SCHEME IMPLEMENTATION FOR A SELF-EXCITED ASYNCHRONOUS GENERATOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This work presents an efficient method for wind power converting applications based on a self-excited asynchronous generator (SEAG). In the adopted study, the machine with the rotor driven by an auxiliary prime mover provides active power to an isolated dc-load via a static converter (SC) associated with a dc bus capacitor through its stator. Thus, for a determined load, the converter's required stator voltages are derived by establishing a specific vector control law relative to a new output control variable introduction. The presented simulation results and their corresponding experimental tests demonstrate that the pretended control strategy ensures perfect output dc-bus voltage tracking performances concerning a simultaneous load drift and the mechanical speed profile.
Keywords: Self-excited asynchronous generator; Vector control; Pulse width modulation inverter; Dc-bus voltage regulation; Lead compensator controller design